A Balancing Act: Emotional Challenges in the HR Role. (15th September 2014) - O'Brien, Elaine; Linehan, Carol
Abstract Despite much academic work and the development of multiple typologies, we are still some way from understanding the HR role. There is a dearth of empirical evidence on HR professionals' work and recent models have been criticized for not adequately reflecting the challenges of trying to balance competing stakeholder interests. We approach this lacuna by focusing on an issue that has not been fully considered in relation to HR work – emotion. Drawing on the findings of a broader study into emotional labour, we highlight the emotive challenges inherent in the day‐to‐day practice of HR. We explore the disjunctions between 'felt' emotions and those actually displayed to meet differing stakeholders' expectations. We show how achieving an appropriate emotion display is a challenging pursuit given these competing expectations. Our contribution is to elucidate emotional labour in the under‐researched 'backstage' professional context, and through our emotion focus to extend our understanding of the complexity of the HR role beyond current prescriptive models.